Associations between physical activity and quality of life, mental health indicators, burnout, and vocal fatigue in Spanish university professors - Estela Colado-Tello, María; Gargallo-Ibort, Esther; Dalmau-Torres, Josep María; Jiménez-Boraita, Raúl (BMC Public Health, 2026)
Introduction The teaching profession requires a high level of dedication and involvement. The high work demands they are subjected to become risk factors for their physical and emotional health. Regular physical activity becomes a key protective factor in coping with such demands. Purpose The aim of the study was to analyse the relationship between the level of physical activity and different dimensions of well-being of university professors in Spain. Method The study was carried out on a sample of 1560 university professors (47.39 ± 11.29 years) from thirteen universities belonging to the Spanish Network of Health Promoting Universities. Physical activity, burnout, healthrelated quality of life, stress, anxiety and depression, vocal fatigue and various sociodemographic factors were assessed. Results 15.33% of university professors have low levels of PA, 56.47% have moderate levels, and only 28.20% achieve high levels. Men had a higher proportion of high levels of physical activity than women. Furthermore, the regression analysis identified positive associations between physical activity levels and all dimensions of quality of life. In addition, a higher level of physical activity was associated with lower rates of stress, anxiety, emotional exhaustion, vocal fatigue and physical discomfort in the voice. Conclusions These results highlight physical activity as an essential tool for promoting general health in the university workplace, enabling university professors to adapt more positively to the demands of the academic environment.
Keywords: health; university professors; physical activity; lifestyle habits; mental disorders